2013
DOI: 10.2135/cropsci2012.08.0495
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Line per se and Testcross Performance for Grain Yield of Tropical Maize in Drought and Well‐Watered Trials

Abstract: Abbreviations: 2 e s , error variance; 2 g s , genotypic variance; CML, CIMMYT maize line; H 2 , broad-sense heritability; 2 LP H , broad-sense heritability of line per se performance; 2 TP H , broad-sense heritability of testcross performance; ISE, indirect selection efficiency; LP, line per se performance; OPV, open pollinated variety; QPM, quality protein maize; r g , genotypic correlation; r g (LP,TP) , ; genotypic correlation between line per se performance and testcross performance; r p , phenotypic cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 31 publications
2
14
0
4
Order By: Relevance
“…This is in accordance with the quantitative genetic theory where the genetic coefficient of variation is expected to be about four times more in inbred lines than that of testcrosses (Miedaner et al, 2014;Smith, 1986). Most of the studies focussing on comparison between lines per se performance and testcross performance in maize under stress have always used elite inbred lines with prior information on performance and heterotic grouping (Betrán et al, 2003;Kebede et al, 2013;Parentoni et al, 2010). This would imply that our tester was generally well performing, thus masking a high frequency of unfavorable alleles in the testcrosses (Smith, 1986).…”
Section: Reduced Genetic Variation For Grain Yield Under Low P In Tessupporting
confidence: 74%
See 1 more Smart Citation
“…This is in accordance with the quantitative genetic theory where the genetic coefficient of variation is expected to be about four times more in inbred lines than that of testcrosses (Miedaner et al, 2014;Smith, 1986). Most of the studies focussing on comparison between lines per se performance and testcross performance in maize under stress have always used elite inbred lines with prior information on performance and heterotic grouping (Betrán et al, 2003;Kebede et al, 2013;Parentoni et al, 2010). This would imply that our tester was generally well performing, thus masking a high frequency of unfavorable alleles in the testcrosses (Smith, 1986).…”
Section: Reduced Genetic Variation For Grain Yield Under Low P In Tessupporting
confidence: 74%
“…Genotypic correlations were computed on the basis of BLUPs from all single trials and the genetic coefficients of correlation between HP vs. LP and/or IBL vs. TC (for simplicity marked as x and y) were calculated according to Cooper et al (1996) and Kebede et al (2013) assuming no environmental covariance between the LP and HP trials due to the experimental set up as: Genotypic correlations were computed on the basis of BLUPs from all single trials and the genetic coefficients of correlation between HP vs. LP and/or IBL vs. TC (for simplicity marked as x and y) were calculated according to Cooper et al (1996) and Kebede et al (2013) assuming no environmental covariance between the LP and HP trials due to the experimental set up as:…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Ketersediaan air yang menurun disertai musim kemarau panjang akibat perubahan iklim berdampak terhadap penurunan produksi jagung pada lahan kering dan tadah hujan. Penurunan produksi jagung akibat kekeringan di daerah tropis berkisar antara 50-80% (Monneveux et al 2006, Iriany et al 2007, Efendi dan Azrai 2010, Kebede et al 2013, Suwardi dan Azrai 2013. Kandungan hara N tanah rendah juga menjadi faktor pembatas upaya peningkatan produksi jagung.…”
Section: Pendahuluanunclassified
“…Both per se performance and combining ability of the inbred parents have been used separately or in combination to predict hybrid performance for different crops including sorghum (Mahama et al, 2014;Kenga et al, 2006); maize (Kebede et al, 2013;Makanda et al, 2010) and rice (Xie et al, 2014). The aforementioned studies have reported positive correlations between inbred per se performance and their hybrid grain yield performance under both drought stress and non-stressed conditions in subtropical and tropical environments.…”
Section: Per Se Performance and Combining Ability Of Inbred Parentsmentioning
confidence: 99%
“…A similar observation has been reported for maize under moisture stressed condition (Betrȃn et al, 2003a). Response to drought stress could therefore be an important selection criterion for lowland adapted genotypes to be used for hybrid development (Kebede et al, 2013). In a recent study, prediction of hybrid grain yield performance based on the component traits has been found promising (Prado et al, 2013).…”
Section: Per Se Performance and Gca Of Locally Adapted Genotypes As Pmentioning
confidence: 99%